Stúdium lokálnych anestetík CLX. Stanovenie kritickej micelovej koncentrácie (c.m.c.) série piperidinoetylesterov 3-alkoxyfenylkarbámovej kyseliny - Andriaminty, F; Cizmárik, J; Mariscáková, Z (Ceska a Slovenska farmacie, 2002)
We have determined the critical micellar concentration (c.m.c) of the derivates type piperidinoethyl esters 3-alkoxy phenylcarbamic in the medium 0.05 mol/l and 0.2/mol/l NaCl for using spectrophotometry methods in the UV region of the spectrum at temperature T = 25 degrees C and pH = 4.5-5.0. We found the parabolic dependence of the -lin(c.m.c.) on the (n) number of the carbon in the alkoxy substituent chain. Further, we have observed the facility formation of the micelle at the solution of 0.2 mol/l than 0.05 mol/l NaCl.
Keywords: Carbamates; Spectrophotometry, Ultraviolet; micely; anestetika lokální; Anesthetics, Local; karbamáty; Micelles; spektrofotometrie ultrafialová